A PROBE INTO THE INDICATORS OF INTERCULTURAL COMMUNICATIVE COMPETENCE IN AN EFL SELF-STUDY TEXTBOOK - Sezen ARSLAN (Informascope, 2018)
Textbooks play a vital role for teaching about different cultures since they present various regions, people, behavior, conventions, religions, values and some other cultural elements of different societies around the world. This study aimed to investigate the cultural content of a self-study textbook which was designed for Open Education Faculty in Turkey. In the study design the descriptive content analysis was employed in order to explore which aspects of intercultural communicative competence were addressed. The findings pointed out that the major part of many activities focused on cultural aspects. The study also put forward some practical recommendations on what content should be delivered through a textbook in order to develop intercultural communicative competence.